Preventive antiretroviral therapy in non-thalassemia carrier infants exposed to mother-to-child transmission of hiv decreases cord and after delivery red blood production without altering the development of hemoglobin - Pornprasert,S. (Bentham Science Publishers B.V., 2015)
Antiretroviral (ARV) prophylaxis for prevention of mother to child transmission (MTCT) of HIV could affect hemoglobin (Hb) development of infants. A cross-sectional descriptive study was conducted in 24 HIV-infected and 21 HIV-uninfected pregnancies. ARV drugs were administered to HIV-infected pregnancies at 21 weeks of gestational age and at labor. Their infants received zidovudine (ZDV) until 4 weeks of age. Blood samples of ARV-exposed and - unexposed infants were collected at delivery, 1, 2 and 4 months of age. Molecular analyses for α-thalassemia-1 Southeast Asian (SEA) type deletion, β-thalassemia mutations and Hb E were performed for excluding the thalassemia carrier infants. Hemoglobinopathy and Hb A, Hb F and Hb A2 were analyzed by using capillary electrophoresis (CE) while hematological parameters were measured using an automated blood counter. At delivery, 1 and 2 months of age, ARVexposed infants had significantly lower levels of RBC counts than ARV-unexposed infants (3.56 vs 4.90, 2.66 vs 4.62 and 3.01 vs 4.05 x1012/L; P <0.001, <0.001 and 0.001, respectively). At delivery, there was a trend for low hemoglobin level in the group of ARV-exposed infants as compared to the group of ARV-unexposed infants (149 vs 154 g/L; P = 0.09) and the significantly different levels were observed among the two groups at 1 and 2 months of age (89 vs 136 and 87 vs 110 g/L; P < 0.001 and 0.001, respectively). The development of Hb A, Hb F and Hb A2 levels from delivery to 4 months of age among the two groups was not significantly different. Therefore, ARV treatments for prevention of MTCT of HIV decreased RBC counts and hemoglobin but did not alter the development of Hb A, Hb F and Hb A2 of non-thalassemia carrier infants.